Attitude and Knowledge of the Parents of Neonates admitted with Tetanus Neonatorum - S. Dibjosubroto; M. Ruskandi; M.S. Azhali (Paediatrica Indonesiana, 1978)
Knowledge and attitude of 44 parents of neonates admitted with tetanus neonatorum to the Department of Child Health, Dr. Hasan Sadikin General Hospital, Bandung, from January 1975 through April 1976 were evaluated. Twenty-eight (63.7%) cases with tetanus neonatorum were from illiterate and elementary-school educated parents. Fourteen (31.8%) parents were aware of the mode of injection and 12 (27.3%) realized the importance of prevention of the disease; 10 (22.7%) mothers did not join prenatal care; 40 (90.9%) neonates were delivered by "peraji" (indigenous/traditional midwives) and 4 (9.1%) by midwives. The decisions which were made by the parents to choose "peraji" for the delivery and to admit their newborns with tetanus neonatorum to the hospital were found in 85% and 75% of the cases respectively.